The estimation of coherence length for electron-doped superconductor Nd2-xCexCuO4+d - Charikova, T.B.; Harus, G.I.; Shelushinina, N.G.; Sochinskaya, O.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Results of low-temperature upper critical field measurements for Nd2–xCexCuO4+δ single crystals with various x and nonstoichiometric disorder (δ) are presented. The coherence length of pair correlation ξ and the product kFξ , where kF is the Fermi wave vector, are estimated. It is shown that for investigated single crystals parameter kFξ @ 100 and thus phenomenologically NdCeCuO-system is in a range of Cooper-pair-based (BCS) superconductivity.